Supporting smallholder farmer resilience with weather advisory information - Gitau, Kevin; Gitumu, Daniel Macharia; Chilambe, Pedro Anglaze; Koech, Grace Jerotich; Gamoyo, Majambo Jarumani; Milimo, Haazele; Vitalis, Koech; Busienei, Linda; Niza, Banda (2025)
This report addresses the effectiveness of using e-extension mobile SMS advisory service in delivering critical weather and agronomic information to rural smallholder farmers in Zambia. A survey was conducted to assess the impact of SMS advisory service provided to farmers across various regions in Zambia. The survey focused on key areas including the usefulness, timeliness, and comprehension of the messages, as well as farmer behaviour in terms of sharing the messages, adopting recommended practices, and experiencing economic or productivity changes. The SMS advisory service focused on providing weather forecasts, recommended crop varieties, pest and disease management, and alerts for severe weather events. This information is essential for aiding farmers in planning their agricultural activities and improving their resilience to climate-related challenges. Their limited access to critical weather and crop management information has had a greater impact on their rainfed crop production. Such information is vital for making informed decisions to improve productivity and resilience. Farmers in most rural parts of Zambia contend with a host of climate-related challenges, including droughts, floods, unpredictable rainfall, rising temperatures, and extreme weather events. These factors severely disrupt agricultural activities, resulting in crop losses, livestock deaths, and diminished livelihoods. The lack of access to reliable weather information further exacerbates their vulnerability, leaving them ill-prepared to respond to climatic shocks. Dependence on rain fed agriculture and minimal income diversification heighten their exposure to risks, while extreme weather conditions foster the spread of pests and diseases, compounding the challenges to crop yields and overall food security.